Appropriateness of Hemoglobin Cut Off’s for Defining Anemia - Kapil, Radhika (Indian Journal of Community Health, 2017)
The use of the hemoglobin cut-off points permits the identification of populations at greatest risk of anemia. The reference cut off’s of Hb also facilitates the monitoring and assessment of progress towards preventing and controlling iron deficiency. These cut off’s also provides the scientific basis for advocacy for the prevention of anemia. There has been continued discussion about the appropriateness of the Cut Off’s used to define anaemia and their applicability to different populations, which has implications for epidemiological surveillance, monitoring, and targeting (1,2). Haemoglobin concentration is affected by physiological characteristics such as age, sex, and pregnancy status, as well as environmental factors such as smoking and altitude. Several studies have shown that the population distribution of haemoglobin is lower in black people than in white people (1,3,4). Only a few studies from low-income and middle-income countries have, however, examined the applicability of the WHO cut off’s to other populations (4,5). The haemoglobin cut-offs presented in Table-1 are used to diagnose anaemia in individuals in a screening or clinical setting.